Think Piece: Food Gardening and Intergenerational Learning in Times of Uncertainty - Nanna Jordt Jørgensen (Southern African Journal of Environmental Education, 2018)
To people who base their livelihoods on land and animals, climate changes generate experiences of increased livelihood uncertainty. With the point of departure in a case story from the Amanzi for Food project in the Eastern Cape and older case material on community gardens in Port Elizabeth, in this paper I reflect on ways of experiencing and coping with uncertain livelihood conditions. The focus of discussion is the intergenerational interactions and learning processes involved in food gardening and their role in shaping responses to uncertainty which point towards ‘creative solutions’ rather than ‘debilitation’ (cf. Calkins, 2016:2).